Battery Cell Charging Behavior Analysis Using Constant Current and Constant Voltage Methods - Anna Cyntia; Muhammad Imran Hamid; Ayu Elsa Afriyanti (Protek: Jurnal Ilmiah Teknik Elektro)
This study presents a detailed simulation of lithium-ion battery charging using the Constant Current/Constant Voltage (CC/CV) method. MATLAB is used in conjunction with certain mathematical algorithms, such as numerical integration and curve fitting, to simulate the charging process, utilizing parameters including a constant current of 1C and a voltage threshold of 4.2V. The simulation analyzes the charging efficiency, usable capacity, and internal impedance variation under various current levels and voltage thresholds. The CC/CV method is compared with findings from other studies that also used the CC/CV charging technique, highlighting similarities and differences in the results. This analysis reveals that while CC/CV is effective in balancing charging speed and safety, minimizing the risk of overcharging, some studies note challenges related to temperature variations and their impact on battery performance. While CC/CV offers optimal management for lithium-ion battery charging, future research can focus on investigating the long-term effects of CC/CV on battery life under various environmental conditions, considering the findings and methodologies of similar studies.